PENERAPAN PROJECT BASED LEARNING PADA MATERI PENCEMARAN LINGKUNGAN TERHADAP KEMAMPUAN MEMECAHKAN MASALAH - Maya Rusiana; Hanum Mukti Rahayu; Ari Sunandar (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Because the residents of Sungai Rasau sub-district constantly run out of water to satisfy their daily requirements when the dry season arrives, this project-based learning takes the shape of creating a filtration tool. The purpose of this study is to ascertain how the project-based learning approach has affected the student's capacity to solve problems related to environmental pollution at SMAN 5 Singkawang. With a single group pretest type—tests and observation sheets—this study approach employs an experimental pre-experimental design. According to the study's findings, the average pretest score was 47.49, while the average posttest score was 76.37. An N-Gain rating of 1.11 indicates improved problem-solving skills (high). The impact size calculation yields a value of 4.02 (high). In class X SMA Negeri 5 Singkawang, it can be inferred that the project-based learning approach significantly influences students' problem-solving skills and their understanding of environmental degradation.